Jackfruit starch: Composition, structure, functional properties, modifications and applications. (January 2021) - Zhang, Yutong; Li, Bo; Xu, Fei; He, Shuzhen; Zhang, Yanjun; Sun, Lijun; Zhu, Kexue; Li, Shize; Wu, Gang; Tan, Lehe
Abstract: Background: There is increasing interest in utilization of jackfruit ( Artocarpus heterophyllus Lam.) starch in applications fields. Jackfruit has potentials as a source of commercially available starches since it is widely cultivated in Asia, Americas and Caribbean with minimal input costs. As the major component of jackfruit seeds (60–80%, dry matter basis) that accounts for 8–15% of the fruit weight, jackfruit starch is considered as cheap and sustainable carbohydrate source. Jackfruit starch (JS) has great potential for various applications due to the unique structural and functional features. Scope and approach: This review aims to highlight the composition, multiscale structure, functional properties, modifications, as well as potential applications of jackfruit starch. In addition, a relationship between functional properties and structure of jackfruit starch is discussed. To expand its potential utilization, future research interests on jackfruit starch are also proposed. Key findings and conclusion: JS has high amylose content (22.10–38.34%) makes the JS as a kind of a potential resistant and low digestible starch. JS shows smaller granule size, swelling power and solubility with a round, bell or oval shape. The extraction methods resulted in different components, some properties of JS. The polymorph of JS is A-type. The proportions of short chain are higher than that of cereal starch. JS shows unique structure with high short chains correlated with pasting viscosity. Jackfruit starch has been used as natural source of resistant starch or thicker, gelling agents and stabilizer in food products. Graphical abstract: Image 1 Highlights: Jackfruit starch (JS) shows smaller granule size, swelling power and solubility. The extraction methods resulted in different components, some properties of JS. JS has high amylose content, high resistant starch content, low digestibility. JS shows unique structure with high short chains correlated with pasting viscosity. The JS can be used in the industries based on its special function properties.